IMPACT OF DEMOGRAPHIC VARIABLES ON MULTI-LITERACY EMPOW ERMENT OF YOUNG LEARNERS - Onovughe, Ofodu Graceful (Sokoto Educational Review, 2018)
The paper examined the influence of demographic variables on multiliteracy empowerment of primary school pupils in Ekiti State. Six hypotheses were generated for the study. The descriptive research design of the survey type was used for the study. A self designed questionnaire was used to elicit responses from the respondents. Section A of the instrument dealt with the name of the pupil’s school, class, sex, age; while section B dealt with the pupil’s parents’ educational level, occupation, school environment etc. The reliability of the instrument was ensured through the test re-test reliability method and a reliability co-efficient of 0.70 was obtained. Data collected were analysed using Chi-square. Findings revealed that there was significant relationship between parents’ educational level, occupation, school environment and pupils’ multiliteracy development. The result showed that there was no significant relationship between pupils’ age, gender and multiliteracy development. Based on the findings, it was recommended that all the variables that could assist these young learners must be properly harnessed in order not to discourage them from learning. Also, since parents and schools play significant roles in the literacy development of children they should utilize the opportunity by providing all the necessaiy literacy materials for their development.